2002
DOI: 10.1159/000064516
|View full text |Cite
|
Sign up to set email alerts
|

Separation of two Cl<sup>–</sup> Currents in Cultured Human and Murine Mesangial Cells: Biophysical and Pharmacological Characteristics of I<sub>Cl.vol</sub> and I<sub>Cl.Ca</sub>

Abstract: Mesangial cells, a combined smooth muscle- and fibroblast-like phenotype, are important regulators of renal function. These cells exist in a region of variable osmolarity and may require Cl channels for volume regulation. Additionally, Ca2+-activated Cl channels in these cells may participate in Ca2+-dependent contractile responses to vasoactive agonists. Relatively little, however, is known about mesangial cell Cl currents (ICl); including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Second, the apparent affinity of sustained contractile responses was higher for UDP compared to UTP (Fig. 3B), which is consistent with the rank-order potency for P2Y 6 rather than for other UTP-and UDP-sensitive receptors, such as P2Y 2 and P2Y 4 [40,43]. Third, UTP-induced constrictions were sharply suppressed in the presence of 10 μM MRS2567 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Second, the apparent affinity of sustained contractile responses was higher for UDP compared to UTP (Fig. 3B), which is consistent with the rank-order potency for P2Y 6 rather than for other UTP-and UDP-sensitive receptors, such as P2Y 2 and P2Y 4 [40,43]. Third, UTP-induced constrictions were sharply suppressed in the presence of 10 μM MRS2567 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…A study using the whole cell patch-clamp configuration in both human MC and a cell line from SV40transformed mice provided evidence for a I Cl.vol that is distinct from I Cl.Ca (12). These investigators found that buffers that prevented an increase in intracellular Ca 2+ uncovered an outward-rectifying Clcurrent that was dependent on osmolarity (12). This volume-sensitive Clcurrent may have been the same Ca 2+ -independent Clcurrent that was identified (under both permissive and nonpermissive growth conditions) in MC harvested from H-2K b -tsA58 transgenic mice in an earlier study (7).…”
Section: Volume-regulated Clchannelsmentioning
confidence: 90%
“…This volume-sensitive Clcurrent may have been the same Ca 2+ -independent Clcurrent that was identified (under both permissive and nonpermissive growth conditions) in MC harvested from H-2K b -tsA58 transgenic mice in an earlier study (7). Pharmacologically, the I Cl.vol could be distinguished from I Cl.Ca by its sensitivity to block by tamoxifen, an estrogen receptor agonist, with an IC 50 of 1 M for I Cl.vol and an IC 50 of 30 M for I Cl.Ca (12). The I Cl.Ca could be blocked more specifically with niflumic acid with an IC 50 of 0.2 M, compared with an IC 50 of 20 M against I Cl.vol .…”
Section: Volume-regulated Clchannelsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the kidney glomerulus (Fig. 3A ), mesangial cells display intermediate features between those of pericytes and fibroblasts, VSMC and myofibroblasts 86 . Mesangial cells have indeed been proposed to be a specialized type of pericytes 87 , 88 , a notion supported by their lineage-dependence on PDGFB-PDGFRB signaling 89 91 , which is shared with other mural cell lineages.…”
Section: The Relationship Between Fibroblasts and Other Cell Types In...mentioning
confidence: 99%